Chemical constituents from the rhizomes of Curcuma zedoaria and Curcuma purpurascens and assessment of their biological activities / Omer Abdalla Ahmed Hamdi - Omer Abdalla, Ahmed Hamdi (2015)
Curcuma zedoaria (Christm.) Rosc. (local name: Temu putih) and Curcuma purpurascens are two medicinally important plants of the genus Curucma and grow abundantly in Asian countries including Malaysia and Indonesia. These two plants are extensively used in the traditional medicinal practice of Malaysia and many other countries of the world for the treatment of various ailments. Phytochemical investigation of the rhizomes of C. zedoaria and C. purpurascens resulted in the isolation of 27 compounds. C. zedoaria afforded eighteen sesquiterpenes, including eight germacrane type (dehydrocurdione 19, curdione 20, furanodiene 21, furanodienone 22, germacrone 23, germacrone 4,5-epoxide 24, germacrone 1,10-epoxide 25, and zederone 26), four guaiane type (gweicurculactone 41, curcumenol 42, curcumenol second monoclinic 150, isoprocurcumenol 43, and procurcumenol 44), one seco-guaiane (curcuzedoalide 62), one elemane (curzerenone 111), one humulane (zerumbone epoxide 151), one cadianene (comosone II 104), one carabrane (curcumenone 65), and one spirolactone type (curcumanolide 101). The work also resulted in the isolation of three labdane diterpenes (labda-8(17), 12 diene-15, 16 dial 127, calcaractrin A 128, and zerumin A 129, which are reported for the first time from C. zedoaria. Phytochemical investigation of C. purpurascens produced five compounds including one bisabolane (ar-turmernone 74) and one guaiane (zedoalactone B 60) sesquiterpene while the rest three are curcuminoids curcumin 138, bisdemethoxycurcumin 139, demethoxycurcumin 140). A total of 34 compounds were identified through the GC and GC-MS spectroscopic analysis of the essential oil obtained by hydrodistillation of C. putpurascens. The major compounds were ar-turmerone 74 (9.4%), germacrone 23 (13.2%), and turmerone 80 (13.5 %). Supercritical fluid extraction of C. purpurascens rhizomes showed that the optimum parameters for higher yield and selective extraction could be obtained at the temperature of 313 K, with ii the pressure 10.34 MPa and the flow rate of liquid CO2 at 12 ml/min. Open column chromatography on silica gel (CC), thin layer chromatography (TLC), preparative thin layer chromatography (PTLC), high performance liquid chromatography (HPLC), and size exclusion chromatography by Sephadex® (LH-20) were used for the detection and isolation of the compounds. Extensive spectroscopic and chromatographic analysis including 1D and 2D NMR (1H NMR, 13C NMR, DEPT, COSY, HMBC, HSQC, and NOESY), IR, UV, GC-MS, LC-MS were used for the structure elucidation of the isolated compounds. X-ray crystallographic analysis was performed on the second monoclinic crystals of curcumenol (151) which is new dimer crystals isolated from C. zedoaria. Isolated compounds were subjected to cytotoxicity, anti-oxidant and neuroprotective assays. Curcumenol (42) and dehydrocurdione (19) showed the highest protection (100%) against hydrogen peroxide induced oxidative stress in NG108-15 cells at the concentrations of 4 and 8 μM, respectively. In the oxygen radical antioxidant capacity assay, zerumbone epoxide (151) showed the highest level of antioxidant activity with a Trolox equivalent (TE) of 35.41 μM per 100 μg of sample. In the MTT based cytotoxicity assay against four cancer cell lines (CaSki, MCF-7, PC-3 and HT-29) curcumenol (42) and curcumenone (65) displayed strong antiproliferative activity (IC50 9.3 and 8.3 μg/ml, respectively). A quantum chemical study was performed to investigate its relationship with cytotoxic activity and revealed that the dipole moment (μ), molecular volume (V), molecular area (A), polarizability (α) and hydrophobicity (log P) are the most important descriptors that influence the cytotoxic activity of the compounds under investigation. The essential oil obtained the hydrodistillation exhibited strong cytotoxicity against HT29 cells but mild cytotoxicity against the non-cancerous human lung fibroblast cell line (MRC5). The two most active compounds; curcumenol (42) and curcumenone (65), were investigated for their binding to human serum albumin (HSA), a transportation protein of human blood. The spectroflurometric analysis, in conjunction with molecular docking study suggested that both curcumenol (42) and curcumenone (65) could bind to binding sites I and II of HSA with intermediate affinity while site I was the preferred binding site for both molecules.